Rancang Bangun Aplikasi Social Assistance Administration Report Berbasis Web Pada Kantor Kecamatan Sungai Rotan - Yeni Anggreni; Fajriyah Fajriyah; Phinton Panglipur (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The Sungai Rotan District Office is located at Jalan Harapan No. 02 Desa Sukarami Kec. Sungai Rattan Kab. Muara Enim. After conducting research at the Sungai Rotan District Office, it was found that problems regarding the processing of social assistance (bansos) data were still manual. Where employees of the Sungai Rotan District Office still store social assistance (bansos) data, still in the form of files or notes in agenda books and do not have a database where when searching for information, they have to open files or agenda books that are old and take quite a long time. In making this final assignment, the authors designed a social assistance program where research was carried out by observation or interviews. The programming used is Sublime text 3 using the mysql database. The tools in designing this system are Unified Modeling Language (UML), Use Cases, Class Diagrams, Activity Diagrams. So that it can replace a system that is less effective and efficient. It is also hoped that this will facilitate reporting to the sub-district office and report social assistance data.